The Effects of Watching Captioned English Video on Incidental Vocabulary Learning Among Gifted Eight Grade Students of SMPN 3 Bissappu - Yawaningsih, Nur Indri; Dollah, Syarifuddin; Muliati, Andi (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
The objective of this study was to identify the effect of watching captioned English on incidental vocabulary learning among gifted eighth grade students of SMPN 3 Bissappu. Pre-experimental design was used with the population of  SMPN 3 Bissappu eighth grade students in the academic year of 2022/2023. Through the purposive sampling technique 24 students from eight classes were selected as the sample of this study. Meaning and recall vocabulary test which was delivered as the pretest and the post-test was chosen as the instrument. The findings of this study implied that watching captioned English video affect the students’ incidental vocabulary learning. The mean score of students’ pretest was 61.41 which is lower than students’ post-test with a mean of 76. Indicating a 24% of improvement. Which means the students learn vocabulary without the intention of doing so. It could be concluded that watching captioned English video has an effect on increasing students’ incidental vocabulary learning.Key words—Vocabulary, captioned English Video, Incidental Vocabulary Learning